Mixed Method Usability Testing for User Experience and User Interface of AI-Based Supermarket Applications - Rinawiyanti, Esti Dwi; Surjani, Rosita Meitha; Hartono, Markus; Permatasari, Eunike Putri; Chrisma, Angela Carla Viana (Journal of Applied Data Sciences, 2025)
Designing digital apps for businesses, including retail companies, is crucial in the digitalization era. To enhance the customers’ shopping experience, an AI-based digital app for supermarkets has been designed to facilitate customers’ searching for and purchasing goods. AI-based digital apps with a good user interface and user experience design will be very effective because they can enhance the app’s visual appeal. After developing the digital app based on the user’s needs and preferences, usability testing was conducted to assess whether it could overcome the problem and enhance the shopping experience. This study aims to determine the usability of digital apps using mixed methods through qualitative and quantitative methods. The usability testing was conducted quantitatively through Maze software (for seven tasks) and a questionnaire using Nielsen’s aspects, including learnability, efficiency, memorability, accuracy, and satisfaction. The results of the Maze score indicated an 80% success rate and a usability score of 59%. This result refers to a medium usability score, indicating the need for future improvements. The results from the usability testing using the questionnaire showed high scores on learnability (85%), efficiency (80%), and memorability (83%), as well as medium scores on accuracy (60%) and satisfaction (50%). The average score from questionnaires is 72%. Both results implied medium usability scores. After quantitative testing, qualitative data regarding users’ experiences, problems, and expectations using the digital app were collected through interviews and observations. The results of the quantitative and qualitative analysis show that the digital shopping app should improve its layout, ease of use, features like a favorites section, and product descriptions. The findings of this study offer fresh insight into integrating quantitative and qualitative methods. In contrast, quantitative and qualitative testing results can be combined to provide a comprehensive analysis that will help the apps improve.In addition, qualitative data regarding users’ experience, problems and expectations in using the digital application was also collected for completing the quantitative data. Based on the usability measurement, it was found that the supermarket digital application has already met all the usability aspects, from qualitative and qualitative data.